Perancangan Desain Hotel Dengan Konsep Shipping Container Yang Menggunakan Metode Precast Dan Konvensional - Makalew, Andreas; Walelang, Christian Dennis; Rumbayan, Rilya; Peginusa, Stefani Switly (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2023)
The design of hotel building with shipping container concept is designed because in Indonesia, especially in North Sulawesi, there is no hotel building with this concept. The purpose of this research is to create a design, design a cost budget estimate, and calculate the estimated construction time of a hotel building with the concept of shipping containers using precast and conventional methods. Shipping Container is a media storage facility used in the process of moving goods from one place to another. In addition to these objectives in the future, it is hoped that the hotel design with this concept will also attract tourists to North Sulawesi. The application method for this project is to combine precast and conventional methods, then designed using software: AutoCad, SketchUp and Microsof Excel. Through this research, a hotel design with the concept of shipping container with an area of 504 m2 has been produced using precast and conventional methods which include floor plan, front view, side view, cut, and 3D design. The resulting hotel construction cost budget is Rp 2,832,283,455.59 and it takes 29 days to install precast column and beam panels. This research shows that the use of both precast and conventional methods can facilitate and speed up the construction process. Keywords: Hotel, Conventional, precast, shipping container